The effect of slurry erosion wear on boronized alloyed ductile iron (0.019 % Niobium and 0.145 % Vanadium) / Khalissah Muhammad Yusof ... [et al.] - Muhammad Yusof, Khalissah; Abdullah, Bulan; Saad, Nor Hayati; Izzatina, Nasfati (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In this study, the effect on microstructure, hardness and slurry erosion wear of alloyed ductile iron (DI) with addition of 0.019 % of Niobium and 0.145 % of Vanadium before and after boronizing process will be discussed. The specimens of ductile iron (DI) and Nb-V alloyed DI were produced through CO2 sand casting method. Specimens were fully coated with boronizing paste in estimation about 3-5mm thickness and heated using Carbolite furnace at 850 0C and 900 0C for 8 hours holding time. The observations of Microstructures were conducted by using Olympus BX 41M Optical Microscope. Vickers Micro Hardness Tester was used to determine the hardness of the specimens while Slurry erosion wear test was conducted to measure the weight loss of each specimen. Diffusing boron into the iron crystalline lattice leads to the formation of two kinds of iron borides (FeB and Fe2B). The thickest boride layer was detected at sample with temperature of 900 0C. The samples of 900 0C give higher hardness than temperature of 850 0C which are 2500 HV and 2209 HV respectively. Referring to slurry erosion test, samples boronized at 900 ºC had greater wear resistance compared to sample boronized at 850 ºC and as cast. This was attributed by the value of weight losses and surface roughness for the materials. This study had proven that, by increasing the boronizing temperature from 850 0C to 900 0C at 8 hours holding time has a significance effect to the boride layer thickness, hardness and wear resistance of alloyed ductile iron.